Interpreting Symbols and Artistic Identity in Led Zeppelins 'Stairway to Heaven': A Semiotic Analysis within an Educational Context Based on Roland Barthes Theory - Ilham Anwar, Iqo; Sinaga, Syahrul Syah (Universitas Syiah Kuala, 2025)
This study explores the symbolic meanings embedded in the lyrics of Stairway to Heaven by Led Zeppelin through the lens of Roland Barthes' semiotic theory. The song was selected due to its rich symbolism and the profound philosophical messages conveyed through both its lyrical content and musical structure. The primary aim of this research is to uncover how Led Zeppelin constructs and conveys their artistic identity through symbolic elements that engage with themes of spirituality, existentialism, and critiques of materialistic culture. Employing a qualitative research method with a descriptive-interpretative design, this study draws data from official lyric documentation, musical references, and media archives. The analysis focuses on three layers of meaning in the lyrics: (1) denotation as literal meaning, (2) connotation as emotional and cultural significance, and (3) myth as an ideological narrative. The findings reveal that the symbol of the